Preparation method of transparent alumina ceramic

By injection molding and heat sintering technology, combined with oxalic acid dehydration technology, the stomach, crystal world and impurities during the sintering process of transparent aluminum aluminum ceramics are solved, and ceramic preparation of high transparency and excellent mechanical properties is achieved.

CN119350000APending Publication Date: 2025-01-24YANCHENG INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411555833.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing transparent alumina ceramic preparation technology has problems with pores, grain boundaries and impurities during the sintering process, and the shape and size of the products prepared by traditional molding methods are limited.

Method used

Use injection molding and heat sintering technology, combined with oxalic acid dehydration technology, prepare aluminum powder through the co -precipitation method of aluminum acetate, ammonium nitrate, and ammonium oxalate, and obtain ceramic slurry through ball grinding and dense refining treatment. Entry molding and heat sintering.

Benefits of technology

Effectively control the micro structure and grain size of ceramics, improve transparency and mechanical properties, eliminate pores and defects, and improve the density and transparency of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350000A_ABST
    Figure CN119350000A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of transparent aluminum oxide ceramics, which comprises the following steps: step 1, adding aluminum acetate into deionized water, then adding an ammonium nitrate solution, finally dropwise adding an ammonium oxalate solution, standing a precipitation solution, filtering, drying, grinding, and sieving to obtain aluminum oxide powder; 2, mixing the alumina powder, a sintering aid and deionized water, adding the mixture into a ball milling tank for ball milling, drying and sieving to obtain mixed alumina powder; step 3, firstly adding an adhesive into an internal mixer for internal mixing until the adhesive is molten, then adding the mixed aluminum oxide powder, and performing internal mixing again to obtain a granulated material; step 4, injection molding; step 5, degreasing; and 6, sintering to obtain the incomplete transparent alumina ceramic. And 7, annealing and sintering to obtain the transparent aluminum oxide ceramic. The transparent alumina ceramic prepared by the invention has high transparency, high density and other excellent properties, and can be widely applied to the field of dental medical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic product preparation, and in particular to a method for preparing transparent alumina ceramics. Background Art

[0002] Transparent alumina ceramics have high hardness, high strength, high wear resistance and excellent corrosion resistance, and are now widely used in many fields such as optics, aerospace, chemistry and chemical engineering, and medical fields. Due to its excellent biocompatibility, transparent alumina ceramics are highly favored in applications such as medical devices and implants.

[0003] The preparation method of alumina powder is crucial to the performance and quality of transparent alumina ceramics. Common preparation methods include vapor deposition, sol-gel method, hydrothermal synthesis method and precipitation method. Among these methods, co-precipitation method is simple to prepare, low cost and has strong controllability in the preparation process. The alumina powder prepared by co-precipitation method has uniform particle distribution and high purity, which provides a high-quality raw material basis for the subsequent preparation of transparent alumina ceramics.

[0004] In terms of alumina ceramic molding technology, compared with traditional dry pressing, extrusion molding and compression molding, injection molding technology has unique advantages, which can achieve high-precision molding of complex structures, reduce subsequent processing steps, and improve production efficiency. At the same time, this technology can also effectively control the shrinkage and deformation of materials to ensure the accuracy and consistency of products.

[0005] Therefore, in the preparation process of transparent alumina ceramics, choosing appropriate powder preparation methods and molding technology is crucial to obtaining high-quality transparent alumina ceramic products. This patent proposes a new preparation method for transparent alumina ceramics, which aims to combine advanced powder preparation technology and efficient molding process to improve the overall performance and production efficiency of transparent alumina ceramics. Summary of the invention

[0006] In order to solve the problems of pores, grain boundaries and impurities in the sintering process of the above-mentioned prior art, as well as the limited shape and size of products prepared by traditional molding methods, the present invention provides a method for preparing transparent alumina ceramics, which can obtain transparent alumina ceramics with high transparency, high density and excellent performance.

[0007] The present invention provides a method for preparing a transparent alumina ceramic, comprising the following steps in sequence:

[0008] Step 1: Add aluminum acetate (Al(CH3COO)3) to deionized water to prepare a 0.5-1.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir well, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours and then filter, dry to obtain alumina powder, grind with a mortar and pass through a 150 mesh sieve to obtain alumina powder;

[0009] Step 2: Mix the alumina powder obtained in step 1 with a sintering aid and deionized water and add them into a ball mill, wherein the mass ratio of the alumina powder, the sintering aid and the deionized water is 1:0.05-0.15:0.3-0.5; add alumina balls into the ball mill to obtain a ceramic slurry, dry the ceramic slurry in a drying oven to a constant weight, and sieve through a 100-mesh sieve to obtain a mixed alumina powder;

[0010] Step 3: first add the adhesive into an internal mixer and mix at 200° C. until it melts, then add the mixed alumina powder obtained in step 2, and mix again to obtain granulated material;

[0011] Step 4: using an injection molding process, injecting the granulated material into a molding mold, setting the injection pressure to 50-100 Bar, the injection temperature to 160-200° C., the holding time to 1-3 min, and taking out the injection mold to obtain an alumina ceramic green body;

[0012] Step 5: using an oxalic acid degreasing process, first immersing the alumina ceramic green body in a 0.5 mol / L oxalic acid solution, and then placing them together in an oxalic acid degreasing furnace, setting the temperature to 400-700° C., and keeping the temperature for 5-12 hours, taking out the alumina ceramic green body, washing the residual oxalic acid with deionized water, and drying to obtain the alumina ceramic;

[0013] Step 6: placing the alumina ceramic in a hot pressing sintering furnace, setting the sintering temperature to 1600-2000° C., the pressure to 50-150 MPa, using argon (Ar) as the pressure transmission medium, and keeping the temperature for 2-6 hours to obtain a non-completely transparent alumina ceramic;

[0014] Step 7: placing the incompletely transparent alumina ceramic in a chamber sintering furnace for annealing and sintering at a sintering temperature of 850 to 1200° C. for a holding time of 4 to 12 hours to obtain a transparent alumina ceramic.

[0015] Furthermore, in the step 1, the dropping rate of NH4C2O4 is 5 ml / min.

[0016] Furthermore, in the step 2, the ball milling speed is 100 to 400 r / min, and the ball milling time is 10 to 24 h.

[0017] Furthermore, the adhesive in step three is at least two of silicone glue (SG), epoxy resin (ER), polyurethane glue (PUA) and polyimide glue (PIA).

[0018] Furthermore, the weight ratio of the alumina powder and SG, ER, PUA, and PIA mixed in the step three is 1:0.1-0.3:0.05-0.15:0.02-0.23:0.04-0.12.

[0019] Furthermore, in the step 3, the granulation temperature is 100 to 260° C. and the time is 3 to 10 hours.

[0020] Furthermore, the sintering aid includes at least two of MgO, La2O3 and Yb2O3.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adopts injection molding and hot isostatic pressing sintering technology to effectively control the microstructure and grain size of ceramics. During the injection molding process, the material is evenly distributed, avoiding the particle accumulation or unevenness that may exist in the traditional pressing process. During the hot isostatic pressing sintering process, the particle size is easy to control, the sample density is uniform, and the mechanical properties are good. Injection molding and hot isostatic pressing sintering technology significantly improve the transparency and mechanical properties of transparent alumina ceramics. Injection molding technology can achieve rapid molding of complex shapes and a highly controllable preparation process, while hot isostatic pressing sintering technology can eliminate pores and defects and improve the density and transparency of the material.

[0023] 2. The present invention adopts oxalic acid degreasing process, the mild nature of which makes it suitable for materials with high requirements and will not cause damage. Secondly, the oxalic acid degreasing process can effectively remove organic matter and dirt. In addition, compared with other high-cost methods, oxalic acid degreasing is low-cost and economical.

[0024] 3. The transparent alumina ceramics prepared by the present invention have high transparency, high density and other excellent properties, and can be widely used in the field of dental medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD pattern of the transparent alumina ceramics prepared in the present invention.

[0026] Figure 2 This is a SEM image of the aluminum oxide powder obtained in the present invention. DETAILED DESCRIPTION

[0027] Advantages and features of the present invention will be illustrated and explained by the following non-limiting description of preferred embodiments thereof, which are given by way of example only with reference to the accompanying drawings.

[0028] Example 1

[0029] The present embodiment provides a method for preparing a transparent alumina ceramic, and the specific steps are as follows:

[0030] Step 1: Add analytically pure aluminum acetate Al(CH3COO)3 into deionized water to prepare a 0.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir thoroughly, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution at a dropping rate of 5 ml / min until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours, filter it, and dry it for 24 hours to obtain alumina powder, grind it with a mortar, and pass it through a 100 mesh sieve to obtain alumina powder.

[0031] Step 2: Mix the alumina powder, MgO, La2O3 and deionized water obtained in the first step and add them to a ball mill. The mass ratio of the alumina powder, MgO, La2O3 and deionized water is 1:0.03:0.02:0.3. Add alumina balls to the ball mill to obtain a uniform ceramic slurry. The ball mill speed is 100r / min and the ball milling time is 24h. Place it in a drying oven and dry it for 8h to constant weight. Pass through a 150μm graded sieve to obtain a mixed alumina powder.

[0032] Step 3: First, add the adhesive composed of silica gel SG and epoxy resin ER into the internal mixer and mix them at 200°C until they melt, then add the mixed alumina powder obtained in the second step, the mass ratio of the mixed alumina powder to SG and ER is 1:0.1:0.05. Mix again at 100°C for 10 hours to obtain a uniform granulated material, which is then granulated on the granulator.

[0033] Step 4: Use the injection molding process to inject the granulated material into the molding mold to ensure that the granulated material fills the shape of the mold. The injection pressure is 50 Bar, the injection temperature is 160°C, and the holding time is 3 minutes. Take out the injection mold to obtain the alumina ceramic green body sample.

[0034] Step 5: Use oxalic acid degreasing process, first prepare 0.5 mol / L oxalic acid solution, soak the alumina ceramic green body in the oxalic acid solution, and then place them together in an oxalic acid degreasing furnace, set the sintering temperature to 400°C, and the insulation time to 12h. Take out the sample, wash the residual oxalic acid with deionized water, and dry it to obtain alumina ceramic.

[0035] Step 6: Using the hot isostatic pressing sintering process, the alumina ceramics are placed in a hot pressing sintering furnace, the sintering temperature is set to 1600°C, the pressure is set to 50 MPa, the inert gas argon Ar is used as the pressure transmission medium, and the heat preservation time is 6 hours to obtain incompletely transparent alumina ceramics.

[0036] Step 7: Place the incompletely transparent alumina ceramics in a chamber-type sintering furnace for annealing and sintering at a sintering temperature of 850° C. for 12 hours to prepare transparent alumina ceramics.

[0037] The total light transmittance of the transparent alumina ceramic prepared in this embodiment reaches 93.22%, and the Vickers hardness reaches 2000 Hv.

[0038] Example 2

[0039] The present embodiment provides a method for preparing a transparent alumina ceramic, and the specific steps are as follows:

[0040] Step 1: Add analytically pure aluminum acetate Al(CH3COO)3 into deionized water to prepare a 1.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir thoroughly, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution at a dropping rate of 5 ml / min until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours, filter it, and dry it for 24 hours to obtain alumina powder, grind it with a mortar, and pass it through a 100 mesh sieve to obtain alumina powder.

[0041] Step 2: Mix the alumina powder, MgO, La2O3, Yb2O3 and deionized water obtained in the first step and add them into a ball mill. The mass ratio of the alumina powder, MgO, La2O3, Yb2O3 and deionized water is 1:0.06:0.02:0.7:0.5. Add alumina balls and mill to obtain a uniform ceramic slurry. The ball mill speed is 400r / min and the ball milling time is 10h. Place it in a drying oven and dry it for 8h to constant weight. Pass through a 150μm graded sieve to obtain a mixed alumina powder.

[0042] Step 3: First, add the adhesive composed of SG and polyimide adhesive PIA into the internal mixer and mix at 200°C until it melts, then add the mixed alumina powder obtained in the second step, the mass ratio of the mixed alumina powder to SG and PIA is 1:0.3:0.12. Mix again at a temperature of 260°C for 3 hours to obtain a uniform granulated material, which is granulated on the granulator.

[0043] Step 4: Use the injection molding process to inject the granulated material into the molding mold to ensure that the granulated material fills the shape of the mold. The injection pressure is 100 Bar, the injection temperature is 200°C, the holding time is 1 min, and the injection mold is taken out to obtain the alumina ceramic green body sample.

[0044] Step 5: Using the oxalic acid degreasing process, first immerse the alumina ceramic green body in the oxalic acid solution, and then place them together in the oxalic acid degreasing furnace, set the temperature to 450°C, and keep the temperature for 12 hours. Take out the alumina ceramic green body, wash the residual oxalic acid with deionized water, and dry it to obtain the alumina ceramic;

[0045] Step 6: Using the hot isostatic pressing sintering process, the alumina ceramics are placed in a hot pressing sintering furnace, the sintering temperature is set to 2000°C, the working pressure is set to 150MPa, inert gas Ar is used as the pressure transmission medium, the insulation time is 2h, and the sintering process is carried out to prepare incompletely transparent alumina ceramics.

[0046] Step 7: Place the sample in a chamber sintering furnace for annealing and sintering at a sintering temperature of 1000°C and a holding time of 10 hours to obtain transparent alumina ceramics.

[0047] The total light transmittance of the transparent alumina ceramic prepared in this embodiment reaches 94%, and the Vickers hardness reaches 2030 Hv.

[0048] Example 3

[0049] The present embodiment provides a method for preparing a transparent alumina ceramic, and the specific steps are as follows:

[0050] Step 1: Add analytically pure aluminum acetate Al(CH3COO)3 into deionized water to prepare a 0.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir thoroughly, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution at a dropping rate of 5 ml / min until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours, filter it, and dry it for 24 hours to obtain alumina powder, grind it with a mortar, and pass it through a 100 mesh sieve to obtain alumina powder.

[0051] Step 2: Mix the alumina powder obtained in the first step with MgO, La2O3, Yb2O3 and deionized water and add them into a ball mill. The mass ratio of the alumina powder, MgO, La2O3, Yb2O3 and deionized water is 1:0.04:0.02:0.02:0.37. Add zirconium oxide ball milling media into the ball mill to obtain a uniform ceramic slurry. The ball milling speed is 240r / min and the ball milling time is 18h. Place it in a drying oven and dry it for 8h to constant weight. Sieve it through a 150μm graded sieve to obtain a mixed alumina powder.

[0052] Step 3: First, add the adhesive composed of polyurethane glue PUA and PIA into the internal mixer and mix at 200°C until it melts, then add the mixed alumina powder obtained in the second step, the ratio of the mixed alumina powder to PUA and PIA is 1:0.08:0.12. Mix again at 200°C for 3 hours to obtain a uniform granulated material, which is granulated on the granulator.

[0053] Step 4: Use the injection molding process to inject the granulated material into the metal mold to ensure that the granulated material fills the shape of the mold. The injection pressure is 75 Bar, the injection temperature is 180°C, and the holding time is 2 minutes. Take out the injection mold to obtain the alumina ceramic green body sample.

[0054] Step 5: Using the oxalic acid degreasing process, first immerse the alumina ceramic green body in the oxalic acid solution, and then place them together in the oxalic acid degreasing furnace, set the temperature to 600°C, and keep the temperature for 10 hours. Take out the alumina ceramic green body, wash the residual oxalic acid with deionized water, and dry it to obtain the alumina ceramic;

[0055] Step 6: Using the hot isostatic pressing sintering process, the alumina ceramics are placed in a hot pressing sintering furnace, the sintering temperature is set to 1730°C, the working pressure is 100MPa, inert gas Ar is used as the pressure transmission medium, the heat preservation time is 6h, and the sintering process is carried out to prepare non-completely transparent alumina ceramics.

[0056] Step 7: Place the sample in a chamber sintering furnace for annealing and sintering at a sintering temperature of 1000°C and a holding time of 10 hours to obtain transparent alumina ceramics.

[0057] The total light transmittance of the transparent alumina ceramic prepared in this embodiment reaches 93.21%, and the Vickers hardness reaches 2160 Hv.

[0058] Example 4

[0059] The present embodiment provides a method for preparing a transparent alumina ceramic, and the specific steps are as follows:

[0060] Step 1: Add analytically pure aluminum acetate Al(CH3COO)3 into deionized water to prepare a 0.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir thoroughly, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution at a dropping rate of 5 ml / min until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours, filter it, and dry it for 24 hours to obtain alumina powder, grind it with a mortar, and pass it through a 100 mesh sieve to obtain alumina powder.

[0061] Step 2: Mix the alumina powder obtained in the first step with La2O3, Yb2O3 and deionized water and add them into a ball mill. The mass ratio of the alumina powder, La2O3, Yb2O3 and deionized water is 1:0.07:0.04:0.35. Add zirconium oxide ball milling media into the ball mill to obtain a uniform ceramic slurry. The ball milling speed is 240r / min and the ball milling time is 12h. Place it in a drying oven and dry it for 8h to constant weight. Sieve it through a 150μm graded sieve to obtain a mixed alumina powder.

[0062] Step 3: First, add the adhesive composed of ER, PUA, and PIA into the internal mixer and mix at 200°C until it melts, then add the mixed alumina powder obtained in the second step, the ratio of the mixed alumina powder to ER, PUA, and PIA is 1:0.08:0.11:0.06. Mix again at a temperature of 180°C for 6 hours to obtain a uniform granulated material, which is granulated on the granulator;

[0063] Step 4: Use injection molding process to inject the granulated material into the metal mold to ensure that the granulated material fills the shape of the mold. The injection pressure is 80 Bar, the injection temperature is 180 ° C, and the holding time is 2 min. Take out the injection mold to obtain the alumina ceramic green body sample;

[0064] Step 5: Using the oxalic acid degreasing process, first immerse the alumina ceramic green body in the oxalic acid solution, and then place them together in the oxalic acid degreasing furnace, set the temperature to 700°C, and keep the temperature for 8 hours. Take out the alumina ceramic green body, wash the residual oxalic acid with deionized water, and dry it to obtain the alumina ceramic;

[0065] Step 6: Using the hot isostatic pressing sintering process, the alumina ceramics are placed in a hot pressing sintering furnace, the sintering temperature is set to 1750°C, the working pressure is 100MPa, inert gas Ar is used as the pressure transmission medium, the heat preservation time is 5h, and the sintering process is carried out to prepare incompletely transparent alumina ceramics.

[0066] Step 7: Place the sample in a chamber sintering furnace for annealing and sintering at a sintering temperature of 1200°C and a holding time of 8 hours to obtain transparent alumina ceramics.

[0067] The total light transmittance of the transparent alumina ceramic prepared in this embodiment reaches 95.02%, and the Vickers hardness reaches 2250 Hv.

[0068] like Figure 1 Shown is the XRD diagram of the transparent alumina ceramic prepared in the present invention.

[0069] like Figure 2 Shown is a SEM image of the aluminum oxide powder prepared in the present invention.

[0070] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solutions formed by equivalent replacement or equivalent transformation shall fall within the protection scope required by the present invention.

Claims

1. A method for preparing a transparent alumina ceramic, characterized in that: The steps are as follows: Step 1: Add aluminum acetate (Al(CH3COO)3) to deionized water to prepare a 0.5-1.5 mol / L solution, add ammonium nitrate (NH4NO3) solution, stir well, add ammonium oxalate (NH4C2O4) solution dropwise to the mixed solution until the mixed solution is fully precipitated, let the precipitated solution stand for 24 hours and then filter, dry to obtain alumina powder, grind with a mortar and pass through a 150 mesh sieve to obtain alumina powder; Step 2: Mix the alumina powder obtained in step 1 with a sintering aid and deionized water and add them into a ball mill, wherein the mass ratio of the alumina powder, the sintering aid and the deionized water is 1:0.05-0.15:0.3-0.5; add alumina balls into the ball mill to obtain a ceramic slurry, dry the ceramic slurry in a drying oven to a constant weight, and sieve through a 100-mesh sieve to obtain a mixed alumina powder; Step 3: first add the adhesive into an internal mixer and mix at 200° C. until it melts, then add the mixed alumina powder obtained in step 2, and mix again to obtain granulated material; Step 4: inject the granulated material into the molding mold, set the injection pressure to 50-100 Bar, the injection temperature to 160-200° C., the holding time to 1-3 min, and take out the injection mold to obtain the alumina ceramic green body; Step 5: first immerse the alumina ceramic green body in a 0.5 mol / L oxalic acid solution, then place them together in an oxalic acid degreasing furnace, set the temperature to 400-700° C., and keep them warm for 5-12 hours. Take out the alumina ceramic green body, wash the residual oxalic acid with deionized water, and dry them to obtain the alumina ceramic. Step 6: placing the alumina ceramic in a hot pressing sintering furnace, setting the sintering temperature to 1600-2000° C., the pressure to 50-150 MPa, using argon (Ar) as the pressure transmission medium, and keeping the temperature for 2-6 hours to obtain a non-completely transparent alumina ceramic; Step 7: placing the incompletely transparent alumina ceramic in a chamber sintering furnace for annealing and sintering at a sintering temperature of 850 to 1200° C. for a holding time of 4 to 12 hours to obtain a transparent alumina ceramic.

2. The method for preparing a transparent alumina ceramic according to claim 1, characterized in that: The dropping rate of NH4C2O4 in step 1 is 5 ml / min.

3. The method for preparing a transparent alumina ceramic according to claim 1, characterized in that: In the step 2, the ball milling speed is 100-400 r / min, and the ball milling time is 10-24 h.

4. The method for preparing a transparent alumina ceramic according to claim 1, characterized in that: The adhesive in step three is at least two of silicone rubber (SG), epoxy resin (ER), polyurethane adhesive (PUA) and polyimide adhesive (PIA).

5. The method for preparing a transparent alumina ceramic according to claim 4, characterized in that: The weight ratio of the alumina powder and SG, ER, PUA, and PIA mixed in the step 3 is 1:0.1-0.3:0.05-0.15:0.02-0.23:0.04-0.

12.

6. The method for preparing a transparent alumina ceramic according to claim 5, characterized in that: In the step 3, the granulation material is mixed at a temperature of 100 to 260° C. for 3 to 10 hours.

7. The method for preparing a transparent alumina ceramic according to claim 1, characterized in that: The sintering aid includes at least two of MgO, La2O3 and Yb2O3.

Citation Information

Patent Citations

  • Preparation method of transparent ceramic self-locking bracket

    CN109650853A

  • Cosolvent assisting degreasing method of light-cured 3D printed aluminum oxide ceramic biscuits

    CN110282985A

  • Alumina ceramic powder with high sintering activity and preparation method therefor

    WO2024045201A1